Menanamkan Karakter Tanggung Jawab Peserta Didik melalui Budaya Organisasi Ikatan Pelajar Muhammadiyah di SMP Muhammadiyah 1 Tulungagung - ‘Iffatuzzahroo’ ‘Iffatuzzahroo’; Suripto Suripto (Journal on Education, 2024)
The lack of awareness of students on their responsibilities in carrying out organizational duties at the Muhammadiyah Student Association resulted in the organization's work program not being able to run properly. This problem is caused by limited human resources, lack of consolidation, communication, coordination between management personnel. As a result, the organizational structure undergoes functional degradation. Various efforts to instill awareness of responsibility, and organizational culture in IPM to students have been carried out through example and guidance by guidance teachers. FORTASI and Taruna Melati activities are activity programs that provide practical experience for students to form their character, responsibility for the tasks charged in organization. This type of research is qualitative research that takes the object of the research location at SMP Muhammadiyah 1 Tulungagung located on Jalan RA Kartini No.35, Kampungdalem, Tulungagung Regency. The results of this study show that the organizational culture built in the Muhammadiyah IPM autonomous organization contributes to the process of leadership regeneration for students at SMP Muhammadiyah I Tulungagung.